Structure and magnetism of copper substituted cobalt ludwigite Co₃O₂BO₃ - Ivanova, N.B.; Kazak, N.V.; Knyazev, Yu.V.; Velikanov, D.A.; Vasiliev, A.D.; Bezmaternykh, L.N.; Platunov, M.S. (Физика низких температур, 2013)
The single crystals Co₃O₂BO₃ with partial (4%) substitution of Co by Cu ions were synthesized by the flux technique. X-ray diffraction and magnetic properties investigations were carried out. The x-ray diffraction meas-urements have shown that Cu clearly prefers only one from four nonequivalent crystallographic positions with the smallest electric field gradient. The ferrimagnetic ordering near TN = 43 K and high magnetic hardness in this magnetic phase are similar to Co₃O₂BO₃. The small reduction of the effective magnetic moment was revealed under copper substitution.